2002
DOI: 10.1152/japplphysiol.00097.2002
|View full text |Cite
|
Sign up to set email alerts
|

H2O2activates ryanodine receptor but has little effect on recovery of releasable Ca2+content after fatigue

Abstract: We studied whether hydrogen peroxide (H(2)O(2)) at Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
1
13
0
2
Order By: Relevance
“…However, we observed inhibition at 40 M, a concentration much lower than inhibition observed in the binding experiments. This enhanced sensitivity of the channel to various compounds is consistent with observations using H 2 O 2 (14,24) and singlet oxygen (31). It is possible that fusing of a SR vesicle to a bilayer lipid membrane modifies the RyR protein in some manner that enhances its sensitivity to channel activators and inhibitors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, we observed inhibition at 40 M, a concentration much lower than inhibition observed in the binding experiments. This enhanced sensitivity of the channel to various compounds is consistent with observations using H 2 O 2 (14,24) and singlet oxygen (31). It is possible that fusing of a SR vesicle to a bilayer lipid membrane modifies the RyR protein in some manner that enhances its sensitivity to channel activators and inhibitors.…”
Section: Discussionsupporting
confidence: 85%
“…Both reagents stimulate Ca 2ϩ release from actively loaded vesicles and stimulate the activity of single Ca 2ϩ channel reconstituted into a bilayer lipid membrane. Oba et al (24) demonstrated activation of channel activity in lipid bilayers at 10 M when the channel was under a controlled redox potential. Still, work in more complete or intact systems has not always supported data derived from isolated SR experiments.…”
mentioning
confidence: 99%
“…Durante el ejercicio, el músculo y el organismo en general se ven sometidos a un gran estrés oxidativo, es decir, hay una pérdida del equilibrio entre la producción de radicales libres y especies reactivas de oxígeno, Acoplamiento excitación-contracción y la capacidad de las células para manejarlos (121)(122)(123)(124). El aumento de los radicales libres parece alterar la liberación de Ca 2+ desde el retículo sarcoplásmico, aunque el efecto sobre la fatiga muscular no está claro (125)(126)(127), además de disminuir la sensibilidad de la miofibrilla al Ca 2+ en mamíferos (128,129). Se han obtenido resultados contradictorios en cuanto al efecto de los radicales sobre la fuerza máxima de la fibra muscular y sobre el Ca 2+ tetánico (128,.…”
Section: El Aumento Del Mg 2+unclassified
“…Skeletal muscle homogenates contain a constitutively active nonphagocytic NAD(P)H oxidase complex that generates superoxide anion (Javesghani et al 2002). Enzymatic or spontaneous dismutation of superoxide anion generates hydrogen peroxide, which markedly activates RyR1 in vitro (Favero et al 1995;Oba et al 2002a) but does not seem to play a significant role in the post fatigue recovery process (Oba et al 2002a). We have found the membrane bound components of NAD(P)H oxidase (gp91 phox and p22 phox ) in skeletal muscle transverse tubules, which are absent from heavy SR vesicles (figure 2).…”
Section: Skeletal Musclementioning
confidence: 99%
“…Endogenous redox-active molecules, including molecular oxygen (Eu et al 2000) and GSSG (Zable et al 1997;Sun et al 2001a,b;Aracena et al 2003), enhance RyR activity. Likewise, H 2 O 2 markedly activates single RyR2 channels (Boraso & Williams 1994) or RyR1 channels maintained under redox control (provided by controlled cytoplasmic and luminal GSH/GSSG ratios; Oba et al 2002a). Furthermore, superoxide anion generation by a NADH oxidase activity that is present in heavy sarcoplasmic reticulum (SR) vesicles and which copurifies with RyR1 channels is presumably responsible for the activation of [ 3 H]-ryanodine binding (a reflection of increased RyR1 activity) produced by 1 mM NADH (Xia et al 2003).…”
Section: Introductionmentioning
confidence: 99%